2015
DOI: 10.7883/yoken.jjid.2014.444
|View full text |Cite
|
Sign up to set email alerts
|

Novel IMB-ELISA Assay for Rapid Diagnosis of Human Toxoplasmosis Using SAG1 Antigen

Abstract: SUMMARY: Nanotechnology is important for medical diagnosis. Various nanoparticles have presented tremendous potential for diagnosing disease markers, pre-cancerous cells, fragment of viruses, specific proteins, antibodies, and other disease indicators. In general, nanoparticles are smaller than 1,000 nm and produced from different materials in different shapes such as spheres, rods, wires, and tubes. Our study aimed to develop a novel antigen-capture immunoassay based on IgG polyclonal antibody-coated magnetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 65 publications
0
11
0
Order By: Relevance
“…Sandwich ELISA elicited a sensitivity of 92%, a specificity of 92.7%, a positive predictive value (PPV) of 92%, and a negative predictive value (NPV) of 92.7%. Immunomagnetic bead-ELISA showed sensitivity (98%), specificity (96.4%), PPV (96%), and NPV (98.1%) which were higher than that of sandwich ELISA [13] .…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Sandwich ELISA elicited a sensitivity of 92%, a specificity of 92.7%, a positive predictive value (PPV) of 92%, and a negative predictive value (NPV) of 92.7%. Immunomagnetic bead-ELISA showed sensitivity (98%), specificity (96.4%), PPV (96%), and NPV (98.1%) which were higher than that of sandwich ELISA [13] .…”
Section: Discussionmentioning
confidence: 79%
“…An immunomagnetic bead-ELISA technique utilizing T. gondii IgG polyclonal antibodies coated with magnetic NPs to capture circulating surface antigen 1 gave better results than sandwich ELISA for diagnosis of human toxoplasmosis using SAG1 antigen [13] .…”
Section: Introductionmentioning
confidence: 99%
“…Nanotechnology may improve sensitivity, selectivity, speed, cost, and convenience of diagnostic tests (Hegazy et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Nanotechnology may improve the sensitivity, specificity, speed, cost and convenience of diagnostic tests. Furthermore, nanotechnology has also opened up the possibility of other screening strategies (Hegazy et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…With the evolutionary advances in nanotechnology, IMB based-ELISA has been introduced in order to reduce the total time for analyses and improve the sensitivity [23] . Several publications utilized IMB based-ELISA to isolate nucleic acids, proteins and cells to be used in diagnosis of many parasitic infections as schistosomiasis mansoni [24] , schistosomiasis japonicum [25] , toxoplasmosis [26] , and neurocysticercosis [27] . In 2015, Hegazy et al [26] found that IMB based-ELISA has higher sensitivity (98%), specificity (96.4%), positive predictive value (96%) and negative predictive value (98.1%) than conventional ELISA when evaluated in the diagnosis of human toxoplasmosis using surface antigen (SAG1).…”
Section: Introductionmentioning
confidence: 99%